237 Introduction of video triage of children with respiratory symptoms at a medical helpline. (1st May 2022) - Gren, C; Hasselager, AB; Linderoth, G; Frederiksen, MS; Folke, F; Ersbøll, AK; Gamst-Jensen, H; Cortes, D
Abstract : Background: Calls regarding children make up the relatively largest proportion of contacts to medical call-centers, with calls often concerning respiratory symptoms. Triage of children without visual cues and through second-hand information is difficult, with risks of over- and undertriage. We aimed to test feasibility, acceptance and patient outcome after introduction of video triage of young children at the out-of-hours medical call-center in Copenhagen, Denmark. Method: Prospective quality improvement study, with patients aged 6 months to 5 years with respiratory symptoms enrolled to video or standard telephone triage (1:1). Calculated sample size was 774. The proportion of successful video calls, representing feasibility, and parental acceptance of video participation was registered, along with patient outcome within 48 hours, including adverse events (intensive care unit admittance, lasting injuries, death). Results: We included 617 patients (54% video triage) before the study prematurely was shut-down due to the COVID-19 pandemic. Feasibility was 95.2% and acceptance rate likewise 95.2%. No adverse events were registered in either group. Patients were triaged to stay at home in 63% of video triage calls vs. 58% of telephone triage calls (p=0.19). Within 8 and 24 hours there was a trend towards fewer video triaged than telephone triaged patients assessed at hospitals: 39% versus 46% (p=0.07) and 41% versus 49% (p=0.07), respectively. Conclusion: Video triage of young children with respiratory symptoms at a medical call-center was feasible, acceptable and safe. Video triage can potentially optimize triage and hospital referrals, and might be beneficial in many pediatric call-center contacts. Conflict of interest: None to declare. Funding: Tryg Foundation, Research Foundation of the Capital Region, Research Foundation of Amager-Hvidovre Hospital.